The Role of Spiritual Factors in the Development of Ideal Immunity in Children - Guliston Masharipova (Genius Journals, 2022)
The role of spiritual factors in the development of ideal immunity in adolescents. The author focuses on the spiritual factors of the problem. In particular, the role of spiritual values in enhancing the spiritual qualities of young people is analyzed.
Keywords: Youth; Values; Analyzed; Spiritual Values